1993
DOI: 10.1071/pp9930621
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinins in Plant Pathogenic Bacteria and Developing Cereal Grains

Abstract: Cytokinin analysis by immunoaffinity chromatography (IAC), high-performance liquid chromatography (HPLC) and radioimmunoassay (RIA) or enzyme-linked immunosorption assay (ELISA) has been used to study two separate topics: the role of tRNA in bacterial cytokinin biosynthesis and the changes in cytokinin concentration which occur during cereal grain development. Transfer RNA isopentenylation in the gall-forming plant pathogen Agrobacterium tumefaciens is encoded by the chromosomal miaA locus. Mutation of miaA re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 52 publications
2
58
0
1
Order By: Relevance
“…Our results confirmed early reports (Saha et al, 1986;Morris et al, 1993) that cytokinin contents in rice grains showed a transient increase at early grain filling stage. Our own earlier work (Yang et al, 2000c) with the same rice cultivars observed that maximum cell division rate in endosperm occurred 10 to14 DPA at NN and 12 to 18 DPA at HN.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our results confirmed early reports (Saha et al, 1986;Morris et al, 1993) that cytokinin contents in rice grains showed a transient increase at early grain filling stage. Our own earlier work (Yang et al, 2000c) with the same rice cultivars observed that maximum cell division rate in endosperm occurred 10 to14 DPA at NN and 12 to 18 DPA at HN.…”
Section: Discussionsupporting
confidence: 82%
“…), high levels of cytokinins are generally found in the endosperm of developing seeds, which may be required for the cell division during the early phase of seed setting (Yang et al, 2000a). Morris et al (1993) reported that zeatin (Z) and zeatin riboside (ZR) in developing rice (Oryza sativa) and wheat (Triticum aestivum) grains showed large transient increases following pollination, which coincided with the period of seed setting and maximum endosperm cell division.…”
mentioning
confidence: 99%
“…It has been proposed that CK controls seed size by influencing cell number in very young, developing seeds. Increased cell number would enhance storage capacity (Morris et al, 1993;Brenner and Cheikh, 1995). Studies of corn, wheat, and rice (Morris et al, 1993) show that CK content is highest during developmental stages that encompass periods of the most rapid nuclear and cell division of the endosperm.…”
Section: Cis-isomers Of Cytokinin Predominate In Chickpea Seedsmentioning
confidence: 99%
“…Increased cell number would enhance storage capacity (Morris et al, 1993;Brenner and Cheikh, 1995). Studies of corn, wheat, and rice (Morris et al, 1993) show that CK content is highest during developmental stages that encompass periods of the most rapid nuclear and cell division of the endosperm. CK levels are greatest at the early endospermic fluid stages of seed growth in lupin (Davey and van Staden, 1978).…”
Section: Cis-isomers Of Cytokinin Predominate In Chickpea Seedsmentioning
confidence: 99%
“…Both RIA and ELISA use radioactively labeled antigen (Ag*) and enzyme-coupled antigen (Ag*) to bind with an antibody to form the specific antigen-antibody (Ag*-Ab) complex, following which the hormones are quantified by measurement of radioactivity and enzyme activity. Immunoassay is a highly specific detection method because of the specific Ab-Ag binding property, and is a sensitive and relatively inexpensive alternative for estimation of plant hormone levels [53][54][55]. The specificity of the Ab-Ag interaction is the key factor affecting quantification results.…”
Section: Immunoassaymentioning
confidence: 99%